2019
DOI: 10.1093/icesjms/fsz165
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of jellyfish in 30+ years of Ecopath with Ecosim models

Abstract: A review of the functional role of jellyfish in Ecopath with Ecosim (EwE) models by Pauly et al. [Pauly, D., Graham, W., Libralato, S., Morissette, L., and Deng Palomares, M. L. 2009. Jellyfish in ecosystems, online databases, and ecosystem models. Hydrobiologia, 616: 67–85.] a decade ago concluded that recreation of jellyfish population dynamics in models required additional ecological research and the careful consideration of their unique biology during model construction. Here, amidst calls for ecosystem-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Recent research has highlighted the importance of jellyfish in marine ecosystems (Hays et al, 2018 ; Lamb et al, 2019 ; Milisenda et al, 2014 ). In addition, recently recorded increases in jellyfish have been linked to global change scenarios such as high fishing pressure (Richardson et al, 2009 ) and global warming (Brotz et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has highlighted the importance of jellyfish in marine ecosystems (Hays et al, 2018 ; Lamb et al, 2019 ; Milisenda et al, 2014 ). In addition, recently recorded increases in jellyfish have been linked to global change scenarios such as high fishing pressure (Richardson et al, 2009 ) and global warming (Brotz et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the paucity of consistent long‐term temporal and spatial data on jellyfish is such that there is considerable uncertainty over whether and why jellyfish populations might be increasing (Condon et al, 2012 , 2013 ; Pitt et al, 2018 ; Sanz‐Martin et al, 2016 ). The logistical difficulties in sampling and monitoring these organisms in time and space are mostly responsible for this deficient level of information, hindering our understanding of jellyfish population dynamics (Lamb et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…broadly (Purcell, 2018), but a single study in Prince William Sound, Alaska found that this genus had similar diet composition to A. labiata (Purcell, 2003), similar to what was found in the current study. Gelatinous zooplankton have historically been approximated as a single functional group during whole‐ecosystem studies (Lamb et al, 2019; Pauly et al, 2009), but studies involving multiple gelatinous zooplankton taxa have demonstrated that taxa fill different trophic niches (e.g., Chi et al, 2020; Fleming et al, 2015). Our data provide additional support that when collected in the same region and time, there are both interspecific similarities and differences for gelatinous zooplankton that should be accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some information gaps remain, notably regarding biomass estimates for benthic primary producers, gelatinous plankton, bivalves, crustacean groups, mesopelagic fishes and pelagic sharks, which were not available and represents a major limitation of the present study. This is particularly important for species that are thought to play an important role in marine ecosystems such as gelatinous plankton (Lamb, Hunter et al 2019), mesopelagic fishes (Irigoien, Klevjer et al 2014;Martin, Boyd et al 2020) and pelagic sharks (Dulvy, Baum et al 2008). In addition, pelagic and demersal scientific surveys are carried out in different seasons (spring and autumn, respectively), which J o u r n a l P r e -p r o o f could have important implications in our modelling exercise as distribution and abundance of species could vary seasonally (Lam, Cheung et al 2008;Vilas, Pennino et al 2019).…”
Section: Discussionmentioning
confidence: 99%